Risk of lead exposure from wild game consumption from cross-sectional studies in Madre de Dios, Peru - Axel J. Berky; Emily Robie; Susy Navio Chipa; Ernesto J. Ortiz; Emma J. Palmer; Nelson A. Rivera; Ana Maria Morales Avalos; Joel N. Meyer; Heileen Hsu-Kim; William K. Pan (Elsevier, 2022)
Summary: Background: Studies have shown elevated blood lead levels (BLL) in residents of remote communities in the Amazon, yet sources of lead exposure are not fully understood, such as lead ammunition consumed in wild game. Methods: Data was collected during two cross-sectional studies that enrolled 307 individuals in 26 communities. Regression models with community random effects were used to evaluate risk factors for BLLs, including diet, water source, smoking, sex, age, and indigenous status. The All-Ages Lead Model (AALM) from the Environmental Protection Agency (EPA) was used to estimate background and dose from wild game consumption. Findings: Indigenous status and wild game consumption were associated with increased BLLs. Indigenous participants had 2.52 µg/dL (95% CI: 1.95-3.24) higher BLLs compared to non-indigenous. Eating wild game was associated with a 1.41 µg/dL (95% CI: 1.20-1.70) increase in BLLs. Two or more portions per serving were associated with increased BLLs of 1.66 µg/dL (95% CI: 1.10-2.57), compared to smaller servings. Using the AALM, we estimate background lead exposures to be 20 µg/day with consumption of wild game contributing 500 µg/meal. Lastly, we found a strong association between BLLs and mercury exposure. Interpretation: Consumption of wild game hunted with lead ammunition may pose a common source of lead exposure in the Amazon. Communities that rely on wild game and wild fish may face a dual burden of exposure to lead and mercury, respectively. Funding: Duke Bass Connections, Duke Superfund Centre funded by the National Institute of Environmental Health Sciences (P42ES010356), Duke Global Health Doctoral Scholar's Program, and Hunt Oil provided funding.